Volume 7: CFD and VIV; Offshore Geotechnics 2011
DOI: 10.1115/omae2011-50225
|View full text |Cite
|
Sign up to set email alerts
|

Flow Induced Forces on Multi-Planar Rigid Jumper Systems

Abstract: Rigid subsea jumper systems are typically used as interface between subsea structures and are required to accommodate significant static and dynamic loads. Due to constraints imposed by in-line planar jumpers (e.g. U shaped and M shaped jumpers), the industry is shifting towards the use of multi-planar jumper systems (e.g., Z-shaped jumpers). These multi-planar jumper systems have increased tolerance to end displacements and can be tailored to accommodate cyclic end motions of subsea structures. Multi-planar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Jia et al [20] set the length and frequency of the slug by numerical simulation to study the interaction characteristics of the two gas-liquid phases in the jumper interior. Nair et al [21] carried out numerical simulations on the slug in a multi-plane jumper and used a finite element model (FEM) to analyze the fatigue damage of the jumper. Pontaza et al [22] conducted a three-dimensional numerical simulation of the vibration process caused by the slug flow in the jumper, estimated the structural response of the jumper, including the fatigue life, and found that the main frequency of the pipe vibration was related to modes 1-4, and the stress is highest when the gas volume fraction was 55%.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al [20] set the length and frequency of the slug by numerical simulation to study the interaction characteristics of the two gas-liquid phases in the jumper interior. Nair et al [21] carried out numerical simulations on the slug in a multi-plane jumper and used a finite element model (FEM) to analyze the fatigue damage of the jumper. Pontaza et al [22] conducted a three-dimensional numerical simulation of the vibration process caused by the slug flow in the jumper, estimated the structural response of the jumper, including the fatigue life, and found that the main frequency of the pipe vibration was related to modes 1-4, and the stress is highest when the gas volume fraction was 55%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on multi-planar jumpers were rare, and only a few numerical analyses on internal flow characteristics such as slug flow were carried out by Wang, et al [30], Dai, et al [31], Lu, et al [32], and Song, et al [33]. Nair, et al [34] analyzed the vibration fatigue response of a multi-plane jumper structure for an internal Existing studies on the vibration of subsea pipelines mainly focus on in-line planar pipelines and the corresponding vortex-induced vibrations caused by the oscillatory lift force generated by the vortex shedding [17][18][19][20][21][22]. With the development of deepwater oil and gas exploitation technology, the pressure and flow rate in the pipeline gradually increase.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on multi-planar jumpers were rare, and only a few numerical analyses on internal flow characteristics such as slug flow were carried out by Wang, et al [30], Dai, et al [31], Lu, et al [32], and Song, et al [33]. Nair, et al [34] analyzed the vibration fatigue response of a multi-plane jumper structure for an internal slug. Numerical simulations of the internal flow in the jumper were carried out to obtain the pressure fluctuations on the jumper, which were used to determine the fatigue damage to the slug.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the one way coupling the exerted fluid loads are not altered by the structure's motion or deformation, the effect of the structural load on the fluid domain is negligible. The difference between the two coupling methods is illustrated in Fig 1 . Recently, FSI has been used extensively in various researches [3][4][5][6][7][8] to investigate the phenomenon of slug flow induced vibration and also vortex induced vibration phenomenon was examined by [9][10][11]. This study aims to investigate the effect of slug flow on pipeline structure using fluid structure interaction technique in Star-CCM+ software.…”
Section: Introductionmentioning
confidence: 99%